Early hospital rehabilitation in patients with a performed intestinal stoma - Kucharczuk, Magda; Sikorska, Hanna; Juraszek, Karolina Małgorzata; Tkaczyński, Karol (Journal of Education, Health and Sport, 2019)
An intestinal stoma is an intentional connection between the light of the small intestine (ileostomy) or the large intestine (colostomy) and the skin surface. The aim of the study was to present the topic of early hospital rehabilitation in patients who had to have a selected stoma as a result of the procedure. Rehabilitation is a supplement to surgical treatment and conditions good functioning of the patient after surgery. The main components of the therapy are: respiratory exercises, exercises of expectoration and effective coughing, wound stabilization, learning to change position from lying to sitting, anticoagulation exercises, general development exercises, verticalisation. More and more often, the rehabilitation is complemented by the use of kinesiology taping. Properly conducted physiotherapy may bring measurable benefits to the patient in the form of functional improvement and return to efficiency before surgery, or reduction of the degree of disability. The patient improvement plan is subject to constant modification by the therapist and is adapted to the physical and mental abilities of the patient on a given day. An important element in the healing process of patients with a performed stoma is the interdisciplinary care provided by all members of the therapeutic team: a doctor, a nurse, a physiotherapist, a psychologist, a nutritionist.